2008
DOI: 10.1016/j.cell.2008.04.052
|View full text |Cite
|
Sign up to set email alerts
|

LXR Signaling Couples Sterol Metabolism to Proliferation in the Acquired Immune Response

Abstract: Summary We demonstrate here that LXR–dependent sterol homeostasis is a physiologically-regulated determinant of cell proliferation and acquired immune responses. T cell activation triggers simultaneous suppression of the LXR pathway for cholesterol transport and induction of the SREBP pathway for cholesterol synthesis. This coordinated program is engaged in part through induction of the sterol-metabolizing enzyme SULT2B1, expression of which in T cells blocks LXR signaling. Forced induction of LXR target genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
572
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 621 publications
(636 citation statements)
references
References 52 publications
49
572
4
2
Order By: Relevance
“…LXRs regulate inflammation by inhibiting the expression of inflammatory mediators including interleukin-6, nitric oxide synthase and cyclooxygenase 2 (Bensinger et al, 2008;Joseph et al, 2003). Mechanistically, the antiinflammatory effects of LXRs have been attributed to the inhibition of nuclear factor kappa-B and STAT1-mediated signaling pathways via transrepression (Glass and Saijo, 2010;Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…LXRs regulate inflammation by inhibiting the expression of inflammatory mediators including interleukin-6, nitric oxide synthase and cyclooxygenase 2 (Bensinger et al, 2008;Joseph et al, 2003). Mechanistically, the antiinflammatory effects of LXRs have been attributed to the inhibition of nuclear factor kappa-B and STAT1-mediated signaling pathways via transrepression (Glass and Saijo, 2010;Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study indicates that ABCG1 also plays a key role in the downregulation of T-cell proliferation and activation. 64) Endogenous ABCG1 is reported to localize to the perinuclear region and, in some cases, to be distributed in the plasma membrane of macrophagederived foam cells. 60,65) It has been reported that ABCG1 mediates the efflux of cholesterol from cells to HDL-2 or HDL-3, but not to lipid-poor apolipoprotein A-I (apoA-I), 49) and that ABCG1 redistributes cholesterol to cell-surface domains accessible for removal by HDL.…”
Section: Abcg Proteinsmentioning
confidence: 99%
“…LXR-ABCG1 signaling was reported to regulate sterol metabolism (Bensinger et al 2008). Activation of LXR inhibited the proliferation of T-cells but had no effect on cell viability (Bensinger et al 2008). Since T0901317 did not inhibit the proliferation of CAOV3 ovarian cancer cells treated with siRNA against LXR or LXR (Scoles et al 2010), it is possible that 22(R)-hydroxycholesterol inhibited cell proliferation mainly through activation of LXR, while inhibition of T0901317 may be caused by both LXR and LXR activation.…”
Section: Anti-proliferative Effect Of Lxr Agonists In Cancer Cellsmentioning
confidence: 99%
“…The effective concentrations for 22(R)-hydroxycholesterol to suppress cancer cell growth is within its known physiological range and is much lower than the concentrations to activate other nuclear receptors (Janowski et al 1996). LXR-ABCG1 signaling was reported to regulate sterol metabolism (Bensinger et al 2008). Activation of LXR inhibited the proliferation of T-cells but had no effect on cell viability (Bensinger et al 2008).…”
Section: Anti-proliferative Effect Of Lxr Agonists In Cancer Cellsmentioning
confidence: 99%